Impact of baseline patient characteristics on interventions to reduce diabetes distress: the role of personal conscientiousness and diabetes self‐efficacy. Issue 6 (25th February 2014) - Fisher, L.; Hessler, D.; Masharani, U.; Strycker, L.
Abstract Aims To improve patient‐centred care by determining the impact of baseline levels of conscientiousness and diabetes self‐efficacy on the outcomes of efficacious interventions to reduce diabetes distress and improve disease management. Methods Adults with Type 2 diabetes with diabetes distress and self‐care problems (N = 392) were randomized to one of three distress reduction interventions: computer‐assisted self‐management; computer‐assisted self‐management plus problem‐solving therapy; and health education. The baseline assessment included conscientiousness and self‐efficacy, demographics, diabetes status, regimen distress, emotional burden, medication adherence, diet and physical activity. Changes in regimen distress, emotional burden and self‐care between baseline and 12 months were recorded and ancova models assessed how conscientiousness and self‐efficacy qualified the significant improvements in distress and management outcomes. Results Participants with high baseline conscientiousness displayed significantly larger improvements in medication adherence and emotional burden than participants with low baseline conscientiousness. Participants with high baseline self‐efficacy showed greater improvements in diet, physical activity and regimen distress than participants with low baseline self‐efficacy. The impact of conscientiousness and self‐efficacy were independent of each other and occurred across all three intervention groups. A significant interaction indicated that those with both high self‐efficacy and high conscientiousness at baseline had the biggest improvement in physical activity by 12 months. Conclusions Both broad personal traits and disease‐specific expectations qualify the outcomes of efficacious interventions. These findings reinforce the need to change from a one‐size‐fits‐all approach to diabetes interventions to an approach that crafts clinical interventions in ways that fit the personal traits and skills of individual people.